Analysis of genetic and environmental correlation between leisure activities and cognitive function in aging Chinese twins. (4th March 2022) - Xu, Chunsheng; Wang, Chu; Tian, Xiaocao; Wu, Yili; Zhang, Dongfeng; Pang, Zengchang; Li, Shuxia; Tan, Qihua
Abstract: Objective: Leisure activity has been shown to be beneficial to mental health and cognitive aging. The biological basis of the correlation is, however, poorly understood. This study aimed at exploring the genetic and environmental impacts on correlation between leisure activities and cognitive function in the Chinese middle- and old-aged twins. Methods: Cognition measured using a screening test (Montreal Cognitive Assessment, MoCA) and leisure activities including intellectual and social activity were investigated on 379 complete twin pairs of middle- and old-aged twins. Univariate and bivariate twin models were fitted to estimate the genetic and environmental components in their variance and covariance. Results: Moderate heritability was estimated for leisure activities and cognition (0.44–0.53) but insignificant for social activity. Common environmental factors accounted for about 0.36 of the total variance to social activity with no significant contribution to leisure activity, intellectual activity and cognition. Unique environmental factors displayed moderate contributions (0.47–0.64) to leisure activities and cognition. Bivariate analysis showed highly and positively genetic correlations between leisure activities and cognition (rG =0.80–0.96). Besides, intellectual activity and cognition presented low but significant unique environmental correlation (rE =0.12). Conclusions: Genetic factor had the moderate contribution to leisure activities and cognition. Cognitive function was highly genetically related to leisure activities. Intellectual activity and cognitive function may share some unique environmental basis.